Developing a Cost-Efficient Employee and Project Management System for Small-Scale Software Development Startups - M.R.A. Perera; S.P. Rupasinghe; E.M.S.D. Ekanayake; H.M.S.Y. Nanayakkara; D. I. De Silva; S.Vidhanaarachchi (International Journal of Engineering and Management Research, 2022)
Startups are a vital and significant part of the software development landscape. They are the first to implement and embrace new technologies and changes in existing technologies. Even though the vast majority of startups are minor in scale, they represent a significant market share. They develop innovative products within a limited time frame with less capital. Their need to work within a limited time frame guides most startups to embrace the agile methodology. These companies also work with proprietary data and procedures essential to maintain competitiveness with other companies in the market. Employee management systems can reduce the workload on human resource management, and project management systems can increase the efficiency of software development. Both these systems are essential tools for a startup. Even though many tools provide these functionalities in the market, they were not developed specifically for startups. This research aims to create a single service optimized for a small employee base that can provide both of these functionalities in the most cost-efficient and secure way.